Automated Diet Planner - Sunil Kadam, Sarvesh; Avinash Jadhav, Vignesh; Sunil Yashwantrao, Pranita; Manoj Chinchore, Pranav (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
The majority of people are cautious about what they eat every day. There are now systems available to assist people in controlling their eating habits. In any case, the systems aren’t focused on the client’s specific requirements. Different people will require different dietary requirements or nutrients for their bodies. We have developed a Diet Planning System. The project is about a new web application that combines the functions of a personal wellbeing assistant and a diet planner. This web-based application system will assist users in obtaining data on their nutritional intake. Dietary suggestions will be made for the user depending on diseases and how many calories they require on a daily basis.